2016
DOI: 10.1038/sj.bdj.2016.864
|View full text |Cite
|
Sign up to set email alerts
|

Social media use, attitudes, behaviours and perceptions of online professionalism amongst dental students

Abstract: Use of social media has increased amongst health professionals. This has benefits for patient care but also introduces risks for confidentiality and professional fitness to practise. This study aimed to examine dental student attitudes towards professional behaviour on social media. The secondary aim was to establish the extent and nature of social media use and exposure to potentially unprofessional behaviours. A cross-sectional study was carried out in one dental school. Data were collected using questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
108
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(125 citation statements)
references
References 24 publications
9
108
1
7
Order By: Relevance
“…Fraping, deliberate posting of inappropriate material on Facebook, after hacking into someone else's account is a new emerging cyber-crime (7). This bring up another aspect of security of cyber networking that can safe-guard public's privacy and self-esteem (24). A study has shown extremely poor awareness about privacy regulations of social media among surgical trainees and established surgeons (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fraping, deliberate posting of inappropriate material on Facebook, after hacking into someone else's account is a new emerging cyber-crime (7). This bring up another aspect of security of cyber networking that can safe-guard public's privacy and self-esteem (24). A study has shown extremely poor awareness about privacy regulations of social media among surgical trainees and established surgeons (27).…”
Section: Discussionmentioning
confidence: 99%
“…1. Usage of social media by healthcare professionals and students (1,7, By and large, the usage of social media by health professionals has escalated during the last decade (1,7,, there is a negative impact of social media usage on medical professionalism as re ected by erosion of professional integrity (11,17,21,(25)(26)(27)(37)(38)(39)(40)(41), an upsurge of awareness about professional identity but rise in unprofessional behaviors in the digital era (7,11,13,18,21,24,27,39,40,43,44) and some evidence of enhanced acquisition of knowledge about digital professionalism by incorporating structured modules in curricula (3,11,19,21,24,26,34,40,41,46,47).…”
mentioning
confidence: 99%
“…These instances addressed intensity of pain, actions taken and the cause and effect relationship. Given the rich source of information available on social media, some studies explored the perspectives of on the management of dental fear and anxiety in pediatric patients [21][22][23][24][25][26][27][28][29][30] .…”
Section: Analysis Of Contentmentioning
confidence: 99%
“…, 5,6,7 Others consider social media, especially Facebook and twitter, as a tool for professional development, as a means of accessing information, marketing practices and services, job opportunities, as well as sharing or adding your opinion on issues of interest to you and to other like-minded individuals online. 8,9, However, other social media research has been conducted that has implications for the profession and the patient -practitioner relationship.…”
Section: Introductionmentioning
confidence: 99%